Analysis of Water Carrying Capacity for Regional Planning Development in Malang Regency - Nadia Paramitha Kusumawardhani (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2020)
The increase of population in Malang City has a significant effect on environmental degradation in the buffer zone, Malang Regency. This regency provides natural resources and collect the remnants of human activity from urban areas experiences a declining trend in environmental carrying capacity, thus it makes difficult to meet the needs of its own population. This research was aimed at analyzing the water carrying capacity as the capital base for development planning in Malang Regency. The research method uses the Supply-Demand approach, which means the calculation of the carrying capacity of water based on future needs and current conditions. The result showed that the carrying capacity of Malang Regency indicated this region experienced a water supply deficit of 0.95% per year.